Considering Forgiveness. - Wagner, Aleksandra; Buckingham, Matthew; Carin, Kuoni (New York : Vera List Center for Art and Politics, 2009)
Aghion, Anne ; Anastas, Ayreen ; Bordowitz, Gregg ; Fast, Omer ; Gabri, rene ; Geyer, Andrea ; Godfrey, Mark ; Hayes, Sharon ; Hilal, Sandi ; Petti Alessandro ; Weizman, Eyal ; Hiller, Susan ; Kristeva, Julia ; Lin + Lam ; Olick, Jeffrey K. ; Price, Brian D. ; Taylor, Jane ; Laderman Ukeles, Mierle ; Young-Bruehl, Elisabeth
Kunst, architectuur, mensenrechten, psychoanalyse, sociologie
boek